2023
DOI: 10.2147/jmdh.s421210
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Pediatric Nurses in Saudi Arabia Regarding Child Abuse

Abstract: Background Child abuse, especially when caused by the child’s parents or caregivers, can be either physical, psychological, and/or sexual. Pediatric nurses should be able to identify cases of child abuse, provide appropriate care, and address the issue. Nurses’ knowledge, attitudes in child abuse are essential in safeguarding the well-being and safety of those children. This study aimed to investigate pediatric nurses’ knowledge and attitude about child abuse and actions taken to address such abus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The lack of knowledge emerged as a common barrier to reporting (67.2%). Alharbi and Moussa (2023) [ 10 ] investigated the knowledge and attitude of pediatric nurses in Saudi Arabia regarding child abuse. The study found that pediatric nurses displayed adequate knowledge and a positive attitudes toward child abuse.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of knowledge emerged as a common barrier to reporting (67.2%). Alharbi and Moussa (2023) [ 10 ] investigated the knowledge and attitude of pediatric nurses in Saudi Arabia regarding child abuse. The study found that pediatric nurses displayed adequate knowledge and a positive attitudes toward child abuse.…”
Section: Reviewmentioning
confidence: 99%
“…Attitudes toward CAN appeared to be generally positive among the populations surveyed. The studies conducted by Alkathiri et al [ 9 ], Alharbi and Moussa [ 10 ], and Merwass et al [ 13 ] demonstrated that healthcare professionals, including nurses and healthcare providers, exhibited positive attitudes toward CAN. Notably, pediatric nurses emerged as particularly proactive in recognizing their role in identifying and addressing cases of child abuse.…”
Section: Reviewmentioning
confidence: 99%
“…Based on a survey conducted in 2023 by the Paediatric Nursing Certification Board, it was found that only 65% of paediatric nurses had received official training on the legal elements of care.Furthermore, a mere 55% of them felt sufficiently prepared to handle ethical difficulties. 4 The disparity between the requirement for skills and the abilities currently possessed highlights the crucial importance of focused educational programmes. Structured Teaching Programmes (STPs) provide a promising method for addressing this gap.…”
Section: Introductionmentioning
confidence: 99%